HISTORIOGRAFI HAJI MENURUT AL QUR’AN - John Supriyanto (JIA (Jurnal Ilmu Agama), 2016)
The study, entitled "Historiography Haji According to the Quran" is intended to reveal the whole concept of the historical aspects of the pilgrimage in the Qur'an. The Hajj initially has started since prophetic Ibrahim that expressed by the Qur'an scattered in separate passages. Historically Hajj begins with the history of Abraham which in turn are the basis religious practices (rituals of Hajj), the historical establishment of the Kaaba Baitullah as houses of worship were first built in the history of human religious and historical aspects syi'ar Allah (Propagation on God). Last, Hajj shows how the historicalpilgrimage later became simbols of human obedience and devotion to God in the system of worship of Muslims.